STOCHASTIC APPROACH FOR EVALUATION OF RELIABILITY AND RESIDUAL LIFE OF TRANSPORT STRUCTURES - U. N. Rabtsau (Наука и техника)
In order to ensure maximum efficiency of investments in operation of transport network it is necessary exactly evaluate reliability and residual life of structures. The criteria of residual life which are presently applied for transport structures in the Republic of Belarus do not permit to execute evaluation with required sufficiency of objectiveness.The paper proposes to use reduction value of structure reliability in the process of their operation as an evaluation criterion of their state and residual life. Specification documents regulating the evaluation procedure of transport structure technical state stipulate execution of structure strength calculations in accordance with design data. Such approach for operated structures looks rather ivory-towered because the actual transport loads have a large statistical dispersion, they are characterized by periodicity, dynamic character, they can criss-cross structures and change in time as in short- so in long term prospects as well.Introduction of СТБ ISO 2394-2007 “Reliability of construction structures” on the territory of Belarus has provided an opportunity to pass from deterministic approach on evaluation of reliability and technical state of operated structures that considers virtual impact of substitute design loading on a real structure to probability approach that considers impacts of actual loadings in specific period of time and which can be determined with the help of experiments. Application of reliability parameter as a criterion of transport structure residual life which is determined with the help of probability method will make it possible to improve significantly the evaluation accuracy due mathematical precise accounting of peculiar features pertaining to actual impacts on specific transport structure and thus it will bring criteria for evaluation of transport structure residual life in accordance with the world development level of construction science and technology.